The effect of scopolamine patch use on post-operative voiding function after transobturator slings - Dessie, Sybil G. (Female Pelvic Med Reconstr Surg, 2016)
OBJECTIVES: The aim of this study was to determine whether the use of a pre-operative transdermal scopolamine patch for post-operative nausea and vomiting prophylaxis affects the success of a voiding trial after a transobturator tape sling procedure. METHODS: This study is a retrospective cohort study of adult women who underwent a transobturator tape sling procedure without concomitant procedures from February 1, 2009 through August 1, 2010. The exposed group included all eligible women who received a pre-operative transdermal scopolamine patch. For each exposed woman, we selected the next two consecutive eligible women who did not receive a transdermal scopolamine patch to be included in the unexposed group. The primary outcome was post-operative voiding trial failure. RESULTS: We identified 35 women who met eligibility criteria and used a pre-operative transdermal scopolamine patch, and included 70 women who did not use a pre-operative transdermal scopolamine. A significantly higher proportion of women in the transdermal scopolamine patch group (54.3%) failed their voiding trial than in the group that did not receive transdermal scopolamine (7.1%, P=<0.001). A history of an incontinence procedure, older age and higher body mass index strengthened the association between transdermal scopolamine patch and voiding trial failure. The adjusted model yielded a risk ratio for voiding trial failure of 13.8 (95% CI: 5.2-36.5) for women who received transdermal scopolamine patch compared to those who did not. CONCLUSIONS: The results of this study demonstrate that use of transdermal scopolamine patches for postoperative nausea and vomiting prophylaxis may negatively affect the success of voiding trials after transobturator tape sling procedures.